Behavior of Decision Making of Purchasing the One District One Product (ODOP) Product from Champhon District, Savannakhet Province: https://doi.org/10.69692/SUJMRD1001151 - SOMBOUNSACK, Phoumsaydavone; XAYYALATH, Kaysone; KEOVORABOUTH, Vinai (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to explore the buying behavior of One District One Product (ODOP) and analyze the factors that affect the buying behavior of One District One Product in Champhon District, Savannakhet Province, which includes 3 types of products: natural incense, saving stove and ancient salt. It is a question of opinions from the people of Kaisonpomvihan city, Savannakhet province, using a questionnaire to interview buyers and shopkeepers. Also, there is a mobilization of ideas to promote one city, one product to become a business from producer groups, group heads and village heads. The statistics used for analysis include descriptive statistics: frequency, percentage and inferential statistics used Binary logit regression analysis. The results of the study found that most of the people of KaisonPhomvihan City focus attention on Intellectual products at a moderate level for 48.9%, most of them prefer to buy the saving stove from Buang Thong Village for 72.2%, buy natural incense from Nook Kok Village for 27.8% and 61.1% were introduced by friends, followed by family and relatives for 26.7%. The decision to buy the product is wise because the features of the product are suitable for household needs for 75.6% who will buy immediately when they see the product, the place of purchase is mostly from the grocery store in the merchant's house directly because of the convenience of travel. They also buy at Sawannxay Market and Samakyxai Market in Kaisonphomvihan City, Savannakhet Province cover for 37.8%. The findings of an examination of the variables gender, age, and educational level that influence a one district one product's purchasing behavior in Champhon District, Savannakhet Province; Product, price, location, sales promotion, and customer understanding are factors that influence purchase behavior. The test of model suitability, which resulted in a statistical value of Chi-squared 78.45, Prob = 0.00, indicated that all of the initial variables had an effect on the opportunity to buy a single product in a single district. According to the model's goodness of fit test, 31.2% of the factors influencing (Odop) product's purchasing behavior can be predicted with 100% accuracy using all of the initial variables. The behavior simulation model's forecast, along with the variables influencing the purchasing decisions of a single district's worth of products, is 83.96% accurate. In Champhon District, factors including age, educational level, and customer awareness influence one district one product purchasing behavior. A bachelor's degree or higher will increase the likelihood of a customer purchasing an Odop product by 17.3%, and when a customer has a total of one point of opinion and understanding, the likelihood of a customer purchasing an Odop product in Champhon will increase by 1.3% at the level of statistical significance. These are the results of taking into account each variable.